(untitled) (TAMADDUN NURI JURNALI, 2024)
This article presents a scientific and philosophical analysis of the important priorities of higher education reform in the development strategy of the New Uzbekistan, based on such scientific methods as comparative analysis, observation and a systematic approach, issues related to the implementation of the concept of development of non-state higher education in society are investigated.